2008
DOI: 10.1002/pros.20733
|View full text |Cite
|
Sign up to set email alerts
|

Total and free PSA kinetics in patients without prostate cancer undergoing radical cystoprostatectomy

Abstract: Comparing PSA kinetics after radical cystoprostatectomy with those of radical prostatectomy, it appears that PSA follows the same elimination pattern in both models. In contrast, Free PSA and Free/Total Ratio elimination kinetics' patterns differ between the two surgical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A linear one-compartment model ( Figure 1 ) was used to describe the pharmacokinetics of a protein serum tumor biomarker in blood, including tumor biomarker secretion by tumor cells (and healthy cells, if background biomarker secretion is also present), transfer to the intravascular space, and final degradation and/or removal from the plasma (represented as outflow [ F out ] in the model). By priming the model parameters on the basis of the literature data for two established and well-studied tumor biomarkers, CA125 for ovarian cancer and PSA for prostate cancer, the potential detection limits needed for a proteomic blood test with regards to tumor burden were calculated under varying physiological and assay conditions ( Tables 1 – 4 ) [ 6 – 8 , 14 , 20 – 24 , 26 , 28 – 31 ]. A sensitivity analysis of the model (by varying model parameters over a range of parameter assumptions) resulted in a wide range of minimally detectable tumor sizes depending on the specific chosen conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A linear one-compartment model ( Figure 1 ) was used to describe the pharmacokinetics of a protein serum tumor biomarker in blood, including tumor biomarker secretion by tumor cells (and healthy cells, if background biomarker secretion is also present), transfer to the intravascular space, and final degradation and/or removal from the plasma (represented as outflow [ F out ] in the model). By priming the model parameters on the basis of the literature data for two established and well-studied tumor biomarkers, CA125 for ovarian cancer and PSA for prostate cancer, the potential detection limits needed for a proteomic blood test with regards to tumor burden were calculated under varying physiological and assay conditions ( Tables 1 – 4 ) [ 6 – 8 , 14 , 20 – 24 , 26 , 28 – 31 ]. A sensitivity analysis of the model (by varying model parameters over a range of parameter assumptions) resulted in a wide range of minimally detectable tumor sizes depending on the specific chosen conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The reported sensitivities for clinically available PSA immunoassays range between detection limits of 0.01 ng/ml and 0.1 ng/ml [ 14 , 23 , 24 ]. As mentioned before, the cut-off level for the distinction between healthy and disease depends on whether the blood biomarker is secreted by normal cells or by tumor cells only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, few studies have focused on the value of Tc‐99m HYNIC PSMA SPECT/CT in patients with BR After RP . Moreover, rapid changes in PSA kinetics are an indicator of poor prognosis after RP or radiation therapy . Therefore, it is possible that Tc‐99m HYNIC PSMA SPECT/CT is more likely to be positive not only in patients with high levels of trigger PSA but also in patients with faster changes in PSA kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our data suggest that that routine PSA surveillance is unnecessary following complete removal of the prostate if the serum PSA is initially undetectable postoperatively. Gregorakis et al [11] recently reported on the serum PSA elimination kinetics in a small cohort of patients who underwent RCP without prostate cancer. The authors demonstrated a biphasic elimination pattern for PSA, with an initial rapid exponential phase half-life of 4.27 h and a terminal nonexponential phase half-life of 63 h. Accordingly, these data support the confirmation of an undetectable PSA level at 3 months after RCP for patients with benign prostate pathology, after which it appears that PSA monitoring might be discontinued.…”
Section: Discussionmentioning
confidence: 99%